Autophagy and the (Pro)renin Receptor - Binger, Katrina J.; Muller, Dominik N. (Frontiers in Endocrinology, 2013)
The (pro)renin receptor (PRR) is a newly reported member of the renin-angiotensin system (RAS); a hormonal cascade responsible for regulating blood pressure. Originally, the identification of PRR was heralded as the next drug target of the RAS, of which such therapies would have increased benefits against target-organ damage and hypertension. However, in the years since its discovery several conditional knockout mouse models of PRR have demonstrated an essential role for this receptor unrelated to the renin-angiotensin system and blood pressure. Deletion of PRR in podocytes or cardiomyocytes resulted in the rapid onset of organ failure, eventuating in animal mortality after only a matter of weeks. In both cases, deletion of PRR resulted in the intracellular accumulation of autophagosomes and misfolded proteins, indicating a disturbance in autophagy. In light of the fact that the majority of PRR is located intracellularly, this molecular function appears to be more relevant than its ability to bind to high, non-physiological concentrations of (pro)renin. This review will focus on the role of PRR in autophagy and its importance in maintaining cellular homeostasis. Understanding the link between PRR, autophagy and how its loss results in cell death will be essential for deciphering its role in physiology and pathology.